Manajemen strategi kompetitif dalam membangun citra dan loyalitas nasabah bank syariah - wahyudi, wandi wahyudi (Maliki Interdisciplinary Journal, 2025)
This study aims to investigate the implementation of competitive strategic management in creating both image and customer loyalty in Islamic banks in Indonesia. In facing increasingly intense competition in the banking sector, Islamic banks need to design efficient strategies to enhance their competitiveness. These strategies include product innovation, improving service quality, consistently applying Islamic values, and optimizing digital technology. A positive image of Islamic banks is formed through customer trust in Islamic financial principles, transparency, and a commitment to ethical services. This strong image directly influences the increase in customer loyalty, which is reflected in their willingness to continue using the products and services of Islamic banks and to recommend them to others. This research uses a descriptive qualitative approach with literature studies derived from various journals and relevant sources. The findings show that well-planned competitive strategic management can strengthen the company’s image and build long-term loyalty amid the modern banking industry competition